"One in Christ": Fedsem spiritualities of solidarity - Duncan, Graham (Acta theologica, 2016)
This article focuses on spirituality as the basis of life at the Federal Theological Seminary of Southern Africa (Fedsem) (1963-1993) during the apartheid years, when Fedsem, groups and individuals within it were subjected to regular surveillance and scrutiny. The spiritual life of the seminary, manifested most clearly in its worship life, became its source of strength and sustained its mission and vision: to be and yet, to become “One in Christ”. This was conveyed by means of various forms of denominational and ecumenical solidarity as an expression of Christian love. Many attempts were made to try to understand and formulate policies relating to the practice of spirituality in an ecumenical context. These met with varying degrees of success.